PENGARUH PEMILIHAN LOKASI TERHADAP MINAT KONSUMEN MEMBELI PERUMAHAN (Pada Perumahan Arengka Resident Pekanbaru) - Munadi, Chairul; Ibrahim, Mariaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Property growth in Pekanbaru seen from town growth very make a promise, Economics storey level in Pekanbaru more highly compared to by a other town, so that the ability buy buy storey level in this town is high enough, even is not affected by crisis that happened. In this time which is a lot of expanding in Pekanbaru is middle housing to for, with complete public facility, using system cluster, and conception minimalis.This research is conducted in housing of Arengka Resident, in Muhajirin, Arengka Pekanbaru. Arengka Resident selected by as location of research of because this housing have an affair that is sale of housing of arengka resident do not reach sales target and the happening of sale degradation.In this research is methodologies used by is quantitative and descriptive with program SPSS, where sampel used by that is consumer buying the housing and as source of information is party developer. To determine sampel with method of census sampling. Technics of data collecting of through, observation and kuesioner.From result analyse data covering validity test, reabilitas, and linear regresi modestly, location choice of berpangruh to consumer enthusiasm. Each owning indicator which each other be interconnectedKeyword: location choice, consumer enthusiasm